PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWP STRAY DAN TIPE GIVING QUESTION AND GETTING ANSWER TERHADAP KEAKTIFAN DAN HASIL BELAJAR SISWA PADA MATERI SISTEM EKSKRESI - RISNAYANTI R DJURAMANG (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2018)
The research aimed at investigating the influence of cooperative learning model type two stay two stray and type giving question and getting answer toward the activeness and learning achievement of student on excretion system. The method of research was quasi experimental research. The data were collected through test result and observation. The objects of this research were students at class VIIIA, VIIIB, VIIIC, and VIIID at SMPN 3 Paguyaman. The research result showed that cooperative learning model type two stay two stray, type giving question and getting answer, and the combination between cooperative learning model type two stay two stray and type giving question and getting answer influenced students’ activeness. Meanwhile, cooperative learning model type two stay two stray, type giving question and getting answer, and the combination between cooperative learning model type two stay two stray and type giving question and getting answer also influenced students’ learning achievement which was showed by significance value as 0,000 lower than alpha value as 0,05.